Psychosocial and personal predisposing factors of frostbite injury and associated amputation: a systematic review - Samuel Kwaku Essien; Batholomew Chireh; Chantee Steinberg; Phinehas Omondi; Audrey Zucker-Levin (Injury Epidemiology)
Abstract Objective To date, systematic reviews of frostbite injuries predominantly focus on the treatment of frostbite, which narrows the scope of prevention and disregards the impact of frostbite-related predisposing factors. Comprehensively synthesizing relevant evidence to understand the psychosocial and personal predisposing factors to frostbite injury and related amputation would provide new insight into frostbite injury prevention. This review investigated the psychosocial and personal predisposing factors of frostbite injury and associated amputation. Methods Databases, including Embase, PubMed, and PsycINFO, were systematically searched for relevant studies. Two independent reviewers performed the screening, data extraction, and quality assessment. Inclusion criteria were studies that reported cold injury, predisposing factors for frostbite injury or related amputations, and assessed the relationship between a predisposing factor and the frostbite injury or amputation outcome based on a descriptive or inferential test. Results Thirty-six (36) studies met the inclusion criteria; 29 reported on both frostbite injury and amputations, and seven reported on only frostbite injury. Six psychosocial predisposing factors were observed in 28 out of the 36 studies reviewed, which included people experiencing homelessness, low socioeconomic status, alcohol intoxication/abuse, smoking, psychiatric disorders, and substance use. Personal predisposing factors identified included inadequate/improper winter clothing, delay in seeking medical care, and lack of knowledge of how to deal with the cold. Conclusions While it is crucial to allocate additional resources and research toward improving the treatment of individuals affected by frostbite injuries and associated limb loss, it is equally important to direct efforts toward addressing the psychosocial and personal predisposing factors that predispose individuals to these injuries and amputations.